Pharmacological Mechanisms in Alzheimer's Therapeutics - Cuello, A. Claudio; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
Alzheimer’s is the most common dementia in the elderly. The need for effective therapy of dementia is greater than ever, but there is not, as yet, a drug therapy which can stop or reverse the clinical consequences. There is, however, a great deal of anticipation on the imminent development of effective, disease-modifying therapies. The remarkable progress made by the scientific community in unraveling molecular and cellular aspects of the Alzheimer’s pathology has allowed the identification of a number of promising targets for drug development. Investigation of these targets and the evolution of ongoing strategies to develop efficacious therapies for this devastating neurodegenerative condition is the central theme of Pharmacological Mechanisms in Alzheimer’s Therapeutics. The current and future therapies based on this new knowledge of the Alzheimer’s pathology are dealt with by contributors who have been most influential in bringing this new knowledge and in the development of experimental and presently applied therapies. The book should be of interest to medical professionals and basic scientists alike since it provides ideas about current trends in Alzheimer’s therapeutics to the general public.
Overview of the Alzheimer's Disease Pathology and Potential Therapeutic Targets -- Trial Designs and Outcomes to Monitor Novel Therapeutics in Alzheimer's Disease -- The Pharmacological Treatment of Alzheimer's Disease with Cholinesterase Inhibitors and Memantine -- M1 Muscarinic Agonists: A Comprehensive Therapy Against Major Hallmarks of Alzheimer's Disease -- Cholinergic Neurodegeneration in Alzheimer's Disease: Basis for Nerve Growth Factor Therapy -- The Rationale for Glutamatergic Therapy in Alzheimer's Disease -- Secretases as Pharmacological Targets in Alzheimer's Disease -- ?-Secretase as a Target for Alzheimer's Disease -- The Rationale for an Immunological Approach to Alzheimer's Therapeutics -- Neuroinflammation, Alzheimer Disease, and Other Aging Disorders -- Nonsteroidal Anti-inflammatory Drugs (NSAIDs) and Derived A?42-Lowering Molecules for Treatment and Prevention of Alzheimer's Disease (AD) -- The Potential Application of Antioxidant Agents in Alzheimer Disease Therapeutics -- Apolipoprotein E: A Potent Gene-Based Therapeutic Target for the Treatment of Sporadic Alzheimer's Disease -- Tau Pathology as a Target in Alzheimer's Therapeutics -- Design of Inhibitors of Amyloid-? Misfolding and Aggregation for Alzheimer's Therapy -- Potential Applications of Glycosaminoglycan-Related Compounds in Alzheimer's Disease -- Multifunctional Neuroprotective Drugs for the Treatment of Alzheimer's Disease -- Interpreting Clinical Studies of Putative Therapeutics for Alzheimer's Disease: The Case of Statins and NSAIDs.
Keywords: Pharmacology; Pharmacology/Toxicology.